الإندماج عن الوسطية الدينية في تعلم اللغة العربية بعد كوفيد -19 - Rina Asih Handayani; Miftahuddin Miftahuddin (Vol. 1 No. 1 (2022): Proceeding of International Conference Cultures & Languages 2022, 2022)
Indonesian's cultural wealth is a potential that can contribute to enriching the wealth of the country, it can also be a source of conflict if these resources are not be managed properly and carefully. Facing this, religious moderation is the best solution in dealing with all differences, both extreme and fundamental groups in the midst of a multicultural nation. On the other hand, Arabic as one of the compulsory subjects for Islamic educational institutions from elementary to tertiary levels, is also responsible for guarding the mandate of religious moderation. This is in accordance with what is stated in article 3 of the national education system law number 20 of 2003. This study is intended to create the concept of learning Arabic based on religious moderation. This research is a library research, which tries to examine religious moderation through non-binding literacy sources originating from books, journals and research in any form. The data that has been obtained, analyzed using the method of content analysis with the approach of Discourse Analysis. After an in-depth study, this research resulted in a formula for integrating moderate values ​​in Arabic learning with Banks' five dimensions: material integration, building knowledge, adapting learning methods, reducing prejudice and strengthening school culture and social structure.